Analisis Pembangunan Pariwisata di Kota Sabang Berdasarkan Implementasi Qanun Kota Sabang Nomor 9 Tahun 2019 Tentang Rencana Induk Pembangunan Kepariwisataan Kota Sabang Tahun 2019-2027 oleh Universitas Syiah Kuala - Wahyu Ilahi; Fadhil Fadhil (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the implementation of Sabang City Qanun Number 9 of 2019 concerning the Sabang Tourism Development Master Plan for 2019–2027, particularly in the development of tourism facilities and infrastructure. The study was motivated by the increasing number of tourist arrivals in Sabang City, which has not been fully matched by the equitable distribution and quality of supporting tourism infrastructure. This research employed a qualitative approach using a descriptive method. Data were collected through interviews, observations, and documentation involving the Tourism Office, the Regional House of Representatives (DPRK), the Sabang Free Trade and Free Port Authority (BPKS), business actors, academics, journalists, community leaders, and tourists. Data were analyzed using George C. Edward III's policy implementation theory, which consists of four dimensions: communication, resources, disposition, and bureaucratic structure. The findings indicate that the implementation of the Qanun has been carried out and reflects the local government's commitment to developing the tourism sector, particularly through improving road access, providing basic tourism facilities, and strengthening destination promotion. However, its implementation has not yet been fully optimized. The main challenges include overlapping authority between the Sabang City Government and BPKS, limited regional funding due to low tax compliance among business actors, inadequate maintenance of public facilities, and socio-cultural dynamics in implementing the halal tourism concept. Therefore, stronger inter-agency coordination, enhanced financial capacity, and more integrated tourism governance are necessary to ensure that the objectives of tourism development can be achieved effectively, sustainably, and for the maximum benefit of the community.